PHYSIOTHERAPY STRATEGIES AND CONSERVATIVE MANAGEMENT FOR CERVICAL RADICULOPATHY: A NARRATIVE REVIEW - SRIRAM K; JYOTI S JEEVANNAVAR; SANTOSH S JEEVANNAVAR (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Cervical radiculopathy (CR) is a common neurological disorder arising from compression or irritation of cervical nerve roots. It typically presents with neck and radiating arm pain, sensory disturbances and motor deficits, and its peak incidence occurs between 40 and 50 years of age. The natural history is often self‑limiting, yet the associated pain and functional limitations prompt many patients to seek care. Conservative treatment—including physiotherapy, manual therapy, cervical traction and exercise—is the initial management approach because it aims to relieve symptoms without surgical risks. However, the evidence base for specific physiotherapy strategies remains heterogeneous and sometimes contradictory. This review synthesises current literature on physiotherapy‑based conservative management of CR, summarises outcomes of randomised controlled trials (RCTs) and recent systematic reviews, and highlights research gaps. We searched PubMed, Cochrane Library, PEDro and Google Scholar for studies up to October 2025. Eleven studies including randomized controlled trials, observational cohorts, a case series, and one systematic review were included. Manual therapy combined with exercise consistently reduced pain and disability; mechanical traction provided no additional benefit. In acute CR, semi‑hard collars or physiotherapy led to greater reductions in arm and neck pain than a wait‑and‑see approach. Cervical vertebral mobilisation improved mechanical pain hypersensitivity and disability in chronic CR. Structured postoperative physiotherapy showed only minor benefits compared with standard postoperative care. Despite promising results, evidence quality is low to moderate, and heterogeneity among interventions limits generalisability. Future well‑designed RCTs with long‑term follow‑up are required.